PARTISIPASI MASYARAKAT DALAM PENGOLAHAN ECENG GONDOK DI BENDUNGAN JATILUHUR - Yudhistira Anugerah Pratama; Risna Resnawaty; Santoso Tri Raharjo (Social Welfare Study Program, 2024)
Abstract. One of the strategic locations in West Java, the Jatiluhur Dam, has an impact on increasing the amount of pollution contained in it, including excessive water hyacinths. To deal with this problem, Presidential Regulation Number 60 of 2021 has also been issued. The purpose of this study is to explain community participation based on the four dimensions of participation described by Wilson & Wilde, namely influence, inclusivity, communication, and capacity. Qualitative descriptive methods are used. The results showed that the community participated in the processing of water hyacinths at the Jatiluhur Dam. Capacity is the most dominant dimension, but other factors, such as influence, inclusion, and communication, are still important to develop in capacity development. In addition, the researchers also suggest conducting further research by considering the latest obstacles and potentials to see the effect of statistical participation on community welfare.Keywords: Influence; inclusivity; communication; capacity; water hyacinth. Abstrak. Salah satu lokasi strategis di Jawa Barat, Bendungan Jatiluhur, berdampak pada peningkatan jumlah polusi yang tertampung di dalamnya, termasuk eceng gondok yang berlebihan. Untuk menangani masalah ini, Peraturan Presiden Nomor 60 Tahun 2021 juga telah dikeluarkan. Tujuan penelitian ini adalah untuk menjelaskan partisipasi masyarakat berdasarkan empat dimensi partisipasi yang dijelaskan oleh Wilson & Wilde, yaitu pengaruh, inklusivitas, komunikasi, dan kapasitas. Metode deskriptif kualitatif digunakan. Penelitian ini menunjukkan bahwa masyarakat berpartisipasi dalam pengolahan eceng gondok di Bendungan Jatiluhur. Kapasitas adalah dimensi yang paling dominan, tetapi faktor lain, seperti pengaruh, inklusi, dan komunikasi, masih penting untuk dikembangkan dalam pengembangan kapasitas. Selain itu, peneliti juga menyarankan untuk melakukan penelitian lanjutan dengan mempertimbangkan hambatan dan potensi terbaru guna melihat pengaruh partisipasi secara statistik terhadap kesejahteraan masyarakat.Kata Kunci: Pengaruh; inklusivitas; komunikasi; kapasitas; eceng gondok.